1983
DOI: 10.1002/cyto.990040204
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and detection of parasitized human red cells by automated flow cytometry

Abstract: Rapid and reliable identification of various human red cell parasites is important in many chemotherapeutic and immunologic studies. Because manual microscopic counting is tedious and imprecise, we have developed a simple diagnostic procedure for the automated flow cytometric detection of in vitro infected red cells, using a nucleic acid-binding fluorescent dye, acridine orange. Human malaria (Plasmodium fakiparum)-infected red cells from continuous human erythrocyte culture were incubated at room temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Recognizing these needs, many flow cytometric assays using different DNA-specific dyes have been evaluated. Several reports show YOYO-1 is better than Hoechst 33258 to easily differentiate between uninfected and infected RBC when parasitaemia is low (6,11). Our published data by using FCM indicated that the infected rat erythrocytes with YOYO-1 can be completely separated from uninfected erythrocytes because of its high relative fluorescence intensity of the dye.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Recognizing these needs, many flow cytometric assays using different DNA-specific dyes have been evaluated. Several reports show YOYO-1 is better than Hoechst 33258 to easily differentiate between uninfected and infected RBC when parasitaemia is low (6,11). Our published data by using FCM indicated that the infected rat erythrocytes with YOYO-1 can be completely separated from uninfected erythrocytes because of its high relative fluorescence intensity of the dye.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, if the parasite is inside the cell, its DNA can be stained with specific nucleic acid-binding dyes and detected by flow cytometry (FCM). Different dyes, such as Hoechst 33258 (5), acridine orange (6), thiazole orange (7), or hydroethidine (8), have been considered for the determination of parasitemia in cultures of P. falciparum by FCM. Jacobberger et al (9) used DiOC1, a membrane potential respon-sive dye and Hoechst 33342 to evaluate parasitemia levels in mice (7).…”
mentioning
confidence: 99%
“…Flow cytometry of malaria parasites has appeared to be a sensitive and rapid method to detect, count, and sort cells, infected with Plasmodium spp., after staining of their DNA with fluorescent dyes (Howard and Battye 1979;Brown et al 1980;Saul et al 1982;Myler et al 1982;Whaun et al 1983;Franklin et al 1986). However, the use of this method to establish DNA contents of different stages and the rate of DNA synthesis in parasite populations has been hampered by asynchronicity of infections, presence of multiple infected host cells, and lack of knowledge concerning the process of DNA synthesis in malaria parasites.…”
Section: Introductionmentioning
confidence: 99%
“…However, they require flow cytometers equipped with ultraviolet lasers that are not available in most laboratories. Nonspecific DNA staining agents, such as thiazole orange (7), acridine orange (8)(9)(10), ethidium bromide (11), propidium iodide (12), or hydroethidine (13)(14)(15), have also been used to stain nucleic acids from infected erythrocytes. Recently, YOYO-1, a cyanine dimer, has been added to this list (16).…”
mentioning
confidence: 99%